Kecemasan pada perempuan yang menghadapi menopause; Sebuah tinjauan literatur - Sari, Wulan; Yunitasari, Eva; Putri, Riska Hediyah (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
One of the stages of life that is definitely experienced by every woman is menopause. Menopause is not having menstruation for 12 consecutive months due to ovaries that have progressively failed in producing the hormone estrogen, follicles in the ovary experience decreased activity that can cause menstruation to stop so that women do not menstruate forever (WHO, 2016). Changes that often occur during menopause are physical changes, ranging from hair, eyes, skin to other physical organs. Target physical organs such as problems in the breast and vagina, as well as hot flashes that arise in the body (Hot Flashes). Not only physical changes that occur at menopause but psychological changes also occur at this time. The problems that arise from these psychological changes cause anxiety in most women. This type of research is research using the literature study method or literature review. Analysis using analysis of journal contents. The results of this study the factors that affect anxiety at menopause are physical changes, education, age, knowledge, family support, economic status, number of children, age of menarche, behavioral, cognitive and affective responses. For handling anxiety in menopause can be given hormonal replacement therapy to reduce symptoms and anxiety in menopause, guidance and counseling services. Suggestion: To health workers in Puskesmas or hospitals to provide counseling or guidance and counseling services. So that all mothers can know what menopause is and do activities that can benefit society to reduce the number of women who experience anxiety in dealing with physical, psychological, and sexual changes in menopause.